Plant virus-mediated induction of miR168 is associated with repression of ARGONAUTE1 accumulation - Várallyay, Éva; Válóczi, Anna; Ágyi, Ákos; Burgyán, József; Havelda, Zoltán (The EMBO journal, 2010)
Virus infections induce the expression of ARGONAUTE1 (AGO1) mRNA and in parallel enhance the accumulation of miR168 (regulator of AGO1 mRNA). Here, we show that in virus-infected plants the enhanced expression of AGO1 mRNA is not accompanied by increased AGO1 protein accumulation. We also show that the induction of AGO1 mRNA level is a part of the host defence reaction, whereas the induction of miR168, which overlaps spatially with virus-occupied sectors, is mediated mainly by the Tombusvirus p19 RNA-silencing suppressor. The absence of p19 results in the elimination of miR168 induction and accompanied with the enhanced accumulation of AGO1 protein. In transient expression study, p19 mediates the induction of miR168 and the down-regulation of endogenous AGO1 level. P19 is not able to efficiently bind miR168 in virus-infected plants, indicating that this activity is uncoupled from the small RNA-binding capacity of p19. Our results imply that plant viruses can inhibit the translational capacity of AGO1 mRNA by modulating the endogenous miR168 level to alleviate the anti-viral function of AGO1 protein.